Negative reactions to monitoring: Do they undermine the ability of monitoring to protect adolescents?. (February 2018) - Laird, Robert D.; Zeringue, Megan M.; Lambert, Emily S.
Abstract: This study focused on adolescents' negative reactions to parental monitoring to determine whether parents should avoid excessive monitoring because adolescents find monitoring behaviors to be over-controlling and privacy invasive. Adolescents ( n  = 242, M age = 15.4 years; 51% female) reported monitoring, negative reactions, warmth, antisocial behavior, depressive symptoms, and disclosure. Adolescents additionally reported antisocial behavior, depressive symptoms, and disclosure one to two years later. In cross-sectional analyses, less monitoring but more negative reactions were linked with less disclosure, suggesting that negative reactions can undermine parents' ability to obtain information. Although monitoring behaviors were not related to depressive symptoms, more negative reactions were linked with more depressive symptoms, suggesting that negative reactions also may increase depressive symptoms as a side effect of monitoring behavior. Negative reactions were not linked to antisocial behavior. There were no longitudinal links between negative reactions and changes in disclosure, antisocial behavior, or depressive symptoms.